Geochemical Characterization of Soil and Water in an Agricultural Area for the Sustainable Use of Natural Resources - Ana C. González-Valoys; Tamir Chong; Jonatha Arrocha; Javier Lloyd; Jorge Olmos; Fidedigna Vergara; Medin Denvers; Juan Jaén; Samantha Jiménez-Oyola; Francisco Jesús García-Navarro (Agriculture)
The Herrera township (86.0 km2), located in La Chorrera, is Panama’s leading pineapple production area. Ensuring sustainable agricultural management in this region is crucial for long-term productivity, resource conservation, and environmental protection. This study evaluates soil and irrigation water quality to provide insights into improved management practices. Soil samples were analyzed for pH, EC, OM, SM, CEC, texture, and content of Al, Ca, Cu, Fe, K, Mg, Mn, N, P, Si, Sr, and Zn. Water samples, including surface water and groundwater, were assessed for Ca, Fe, K, Mg, Mn, Na, N, HCO3, SO4, PO4, NO3-N, and salinity. Soil quality was evaluated using the Igeo, and geospatial techniques were applied to map the soil parameter distribution. The water quality analysis confirmed its suitability for irrigation, though groundwater in the central area requires caution due to elevated Na levels and a moderate risk of salinization. Soil maps indicate adequate levels of essential nutrients but highlight the need for N amendments. This study is the first comprehensive assessment of an agricultural township in Panama, providing critical data for decision-making and the adoption of sustainable agricultural practices that enhance resource management and mitigate climate change impacts.